Two rare diseases, acute calcific retropharyngeal tendinitis, and crowned dens syndrome, mimicking meningitis: A case report - Igami, Eriko; Fukae, Jiro; Kanazawa, Kazo; Fuse, Atsuhito; Nakajima, Asuka; Eguchi, Hiroto; Hattori, Nobutaka; Shimo, Yasushi (Frontiers in Neurology, 2022)
We report two rare cases. One involved acute calcific retropharyngeal tendinitis, an inflammatory condition of the longus colli tendon triggered by deposition of calcium hydroxyapatite crystals. The other involved crowned dens syndrome, caused by pseudogout of the atlantoaxial junction following deposition of calcium pyrophosphate dehydrate or calcium hydroxyapatite. Although these two diseases involve different mechanisms, the common symptoms of neck pain and fever resemble those of meningitis. Accurate diagnosis can thus be difficult without background knowledge on these conditions. Cerebrospinal fluid examination and cervical computed tomography are useful for distinguishing these pathologies from meningitis.